An Examination of Linear Combinations of Skew-Adjoint Type Algebraic Curvature Tensors - Brundan, Joseph (The PUMP Journal of Undergraduate Research, 2021)
In this paper a new potential invariant of algebraic curvature tensors, the signature, will be examined. Furthermore, linear combinations of skew-adjoint type algebraic curvature tensors will be thoroughly examined so as to provide some insight into the possible forms of algebraic curvature tensors.